Ukraine : Technical Assistance Report-A Follow-Up on Distributed Profit Tax, BEPS Implementation, Voluntary Disclosure Program, and Indirect Methods for Determining Taxable Income. (IMF Staff Country Reports; Country Report, 2020)
Tax policy in Ukraine is engaged in two fronts at once. On one front, very significant work has been done over the years on the gradual improvement and updating of the tax system; on the other, it questions essential tenets of the existing system, exploring fundamental changes to it. While serious efforts have been devoted, for example, to the modernization of the international aspects of the income tax, upgrading the regime to OECD standards, there is a strong push from some quarters of the policy debate to do away with the Corporate Profit Tax (CPT) altogether. The central idea is to replace it with a Distributed Profit Tax (DPT), generally referred to in Ukraine as the Exit Capital Tax (ECT). In essence, this system would not tax profits as they accrue to the corporation, deferring the tax to when the corporation distributes dividends to the shareholder.